Direct deposition of a nanoporous palladium electrocatalyst for efficient hydrogen evolution reaction. (1st May 2020) - Ehsan, Muhammad Ali; Suliman, Munzir H.; Rehman, Abdul; Hakeem, Abbas Saeed; Yamani, Zain H.; Qamar, Mohammad
Abstract : The porous palladium directly deposited on metallic substrates by aerosol-assisted chemical vapor deposition exhibits remarkable HER performance in an acidic electrolyte. Abstract : The aim of the present study is to produce high performance Pd-based electrodes for water splitting by a simple and fast preparation technique, and to investigate the impact of substrates and film growth time on electrode performance. The electrodes are prepared in one step by the aerosol-assisted chemical vapor deposition (AACVD) method within 30 to 120 min. Pd is deposited on titanium (Ti) foil and nickel foam (NF). Microscopic analyses indicate the growth of cauliflower-like porous nanostructures of Pd. Electrochemical measurements indicate that the Pd/NF electrode requires only 65 mV and 189 mV, while the Pd/Ti electrode requires 121 mV and 288 mV to produce current densities of 50 and 150 mA cm −2, respectively, for the hydrogen evolution reaction (HER). The respective Tafel slopes for Pd/NF and Pt/Ti are determined to be 29.3 mV dec −1 and 52.3 mV dec −1, suggesting different rate-determining mechanisms of the HER on various substrate surfaces. The better activity of the Pd/NF electrode is attributed to higher electrical conductivity of bare NF and Pd/NF electrodes compared to that of bare Ti and Pd/Ti electrodes, though the charge transfer resistances are discerned to be comparable. The turnover frequency of the Pd/NF electrode is superior to that of Pd/Ti at lower overpotential, which becomes comparable with increasing potential. The results of this study combined with our earlier findings reveal the bi-functional electrocatalytic nature of the nanoscale Pd for possible utilization in an electrochemical water splitting unit for H2 and O2 production.